How Is ADHD Assessed and Documented? Examination of Psychological Reports Submitted to Determine Eligibility for Postsecondary Disability. Issue 14 (December 2019) - Nelson, Jason M.; Whipple, Brittany; Lindstrom, Will; Foels, Patricia A.
Objective: To examine how ADHD evaluations are documented for postsecondary students requesting disability eligibility.Method: A total of 100 psychological reports submitted for eligibility determination were coded for documentation of Diagnostic and Statistical Manual of Mental Disorders ( DSM ) criteria, methods and instruments used in the evaluations, and recommended academic accommodations.Results: Results showed that a minimal number of reports (≤1%) documented that students met all DSM criteria for ADHD. Psychologists rarely documented childhood impairment, symptoms across settings, or the use of rule-outs. Symptom severity was emphasized over current impairment. The majority of psychologists utilized a multi-informant, multi-method evaluation approach, but certain methods (e.g., symptom validity tests, record reviews) were limited in use. Most reports included recommendations for academic accommodations, with extended time being the most common (72%).Conclusion: This study raises awareness to the aspects of adequate ADHD evaluation and subsequent documentation that can be improved by psychologists. Recommendations are made regarding valid documentation of ADHD for disability determination purposes.